Vulnerability to HIV infection among the Borana pastoral community of Southern Ethiopia: a persisting challenge - Serbessa MK (Dove Medical Press, 2019)
Mirgissa Kaba Serbessa Department of Preventive Medicine, School of Public Health, Addis Ababa University, Addis Ababa, Ethiopia Background: Vulnerability to HIV infection is a major concern in an effort to control further infections. What drives vulnerability among pastoral settings of Ethiopia is not well documented.Objectives: This study aims to identify drivers of vulnerability to HIV infection among the Borana pastoral community of Ethiopia.Methods: Data were collected during 2008–2009 as part of a PhD work and subsequently in 2014 and 2016, during a follow-up visit to Borana. Data on perceived threats of HIV, facilitators of vulnerability, coping mechanisms and perceived consequences were collected by trained research assistants using topic guides developed for this purpose. In-depth and key informant interviews and Focus Group Discussions (FGDs) with selected married men and women, opinion leaders, and HIV focal persons of public sectors and Non Governmental Organizations in Teltele, Arero, Yabelo and Moyale were carried out. Sample transcripts were checked for consistency and completeness before data collection was completed. Two qualitative researchers read transcripts and suggested themes and subthemes in reference to the objective of the study. Transcripts were imported to MAXQDA software. Thematic analysis was applied to reduce data into defined themes. Findings were interpreted following the objective of the study.Findings: The results show that HIV is a major threat in Borana with individual and community level consequences. Concurrent extramarital sexual practices, men’s role in the selling of livestock and consequent encounters with “other” women facilitate vulnerability to HIV. Lack of information about HIV, availability and use of condoms, and failure to use local resources for HIV prevention were key limitations to coping with the problem. After nearly 40 years of HIV intervention in Ethiopia, coping mechanisms are not exploited in Borana.Conclusion: Vulnerability to HIV among the Borana pastoral community is facilitated by multiple factors that work in tandem, thus calling for interventions that address the different factors at the same time. Keywords: pastoral community, HIV and AIDS prevention, vulnerability, coping mechanisms, threats of HIV, perceived consequences of HIV, facilitators of HIV, pastoral community